Urban Heritage - Authenticity and Civilization (Maysan City, Iraq - Model) (Journal of Misan Researches, 2022)
The importance of heritage lies in all countries, as it represents its cultures and civilizations, as it is considered the artery that links the citizen to his land and it helps to spread the spirit of citizenship and gives him a feeling of belonging to common roots and foundations and too noble goals in general, and thus the architectural heritage is documentation of the history and civilization of the nation, and it must be Preserving and maintaining it in order to make room for the introduction of contemporary and modernity and to achieve the transfers required for civilized progress.                                The importance of dealing with heritage comes through the diversity of its assimilation of the concept of intellectual, civilizational and cultural, and moreover, it is characterized by the enhancement of the confidence of man and society himself. The definition of the citizen and society is a highlight of the great role of Iraqi civilization in building its history and glory